HUBUNGAN PENGETAHUAN DAN SIKAP IBU NIFAS DENGAN PRAKTIK PERAWATAN MASA NIFAS DI KECAMATAN GUNUNGPATI KOTA SEMARANG BULAN JANUARI-MARET 2015 - Sagita Eldawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Posnatal care is necessary thing to do because doing postnatal care in good way will reduce risk of death postpartum mothers.  This research aimed to analyse the relation knowledgment and act postpartum mother with practice postnatal care t in Gunungpati region Semarang city. This was explanatory research with cross-sectional study approach. Population in this research are mother of baby (< age 6 month) in number 113 and sample that be choosen by simple random sampling 53 people. Data Analysis is concluding univariat and bivariat analysis (descriptif and analytic) by using  Chi Square test with yates correction methods,  level of significance 5%. The result of this research, based on result of study show that are mod bad knowledgment postpartum mothers (58,5%), percentage of good postpartum mothers act (52,8%), and practice of bad postnatal care period (56,6%). The largest respondent that is had hight level of  bad knowledge with bad practice of postnatal care (71,0%), that have bad act with practice of postnatal care (76,0%). The result of analysis data is collected there are significant relation about  knowledgment postpartum mother with postnatal care period practice (pvalue = 0,026), there are significant relation of  act postpartum mother with postnatal care period practice (pvalue = 0,016)Recomendation to increase socialization about proceeds posnatal care by interpersonal comunication, implementation does when recitation of quran and arisan PKK.